Damage identification through the comparison with pseudo-baseline data at damaged state. (April 2016) - Lee, Eun-Taik; Eun, Hee-Chang
Abstract Without baseline information prior to damage, the damage should be detected by only measured data. Most non-baseline damage detection methods can be sensitive to the external noise and have difficulty in detecting damage when the sensor is not close to it. The purpose of this study is to propose a non-baseline damage detection method using only a few measurements and being less sensitive to the noise. A set of pseudo-reference data to be established at measurement instant is compared with another set of measurement data on the structure with the additional damage at a known location. The damage is found at the location to represent the abrupt change of the difference in the two response data sets. Compared to the global-deviation method, this method has merits to reduce the noise effect and to be able to detect damage by a few sensors. The experimental work also investigates the sensitivity of accelerometer and strain gage in detecting damage. The proposed method is verified in a numerical application and an experiment.